Computational methods for large systems electronic structure approaches for biotechnology and nanotechnology - Reimers, Jeffrey R. (Wiley, 2011)
"While its results normally complement the information obtained by chemical experiments, computer computations can in some cases predict unobserved chemical phenomena Electronic-Structure Computational Methods for Large Systems gives readers a simple description of modern electronic-structure techniques. It shows what techniques are pertinent for particular problems in biotechnology and nanotechnology and provides a balanced treatment of topics that teach strengths and weaknesses, appropriate and inappropriate methods. It's a book that will enhance the your calculating confidence and improve your ability to predict new effects and solve new problems"--